WINGS OF RESILIENCE: EXPLORING CRISIS COMMUNICATION STRATEGIES ON SOCIAL MEDIA BY LEADING ROMANIAN AIRLINES DURING THE COVID-19 PANDEMIC - Mădălina-Maria TOMA (Association of Social and Educational Innovation, 2024)
This study investigates the crisis communication strategies employed by the leading Romanian airlines - TAROM, WIZZ Air, and Blue Air - on social media during the COVID-19 pandemic. Utilizing the Situational Crisis Communication Theory (SCCT), this research analyzes the content and frequency of the airlines' Facebook posts from February to July 2020. The findings reveal how airlines navigated the crisis by adopting specific communication strategies and engaging with stakeholders, highlighting the importance of digital platforms in maintaining customer relationships during unprecedented challenges.